Corporate Social Responsibility in Cameroon: Practices and Environmental Impact - Peter Fofuh; Olawumi Dele Awolusi (Journal of Education and Vocational Research, 2021)
The purpose of this study is to examine how CSR is practiced by local businesses and their influence on environmental protection and sustainable growth in Cameroon. Grounded on the stakeholder theory, a multi-method data collection tool was used to collect data for qualitative analysis. A thematic content analysis was approached was used in this study to examine the CSR practices of 20 local businesses in Cameroon. Findings from the study revealed that the concept of corporate social responsibility is relatively new and local corporations are not fully equipped to address the needs of their stakeholders. Also, environmental concerns and community issues were not areas of concern to companies when adopting CSR strategies. Additionally, government intervention to enforce existing laws and regulations on environmental and social issues was lacking. The study implies that by neglecting environmental concerns local businesses are endangering the environment and failing to plan for sustainable growth. Besides expanding knowledge about the level of CSR awareness and practice in Cameroon by exposing the limitations of local companies in adopting CSR and the laxity of the government in enforcing the relevant laws and legislation. It is recommended, that to plan for sustainable development and environmental protection, the government should be more proactive in upholding laws and regulations related to environmental protection and businesses, being more ethical in their daily practices. CSR policies should also be codified to encourage and compel businesses on the need for environmental protection by requesting businesses produce mandatory CSR disclosures.